2007
DOI: 10.1002/ijc.23008
|View full text |Cite
|
Sign up to set email alerts
|

ANXA7 expression represents hormone‐relevant tumor suppression in different cancers

Abstract: Tumor suppressor function of ubiquitously expressed Annexin-A7, ANXA7 (10q21) that is involved in exocytosis and membrane fusion was based on cancer prone phenotype in Anxa7(1/2) mice as well as ANXA7 role in human prostate and breast cancers. To clarify ANXA7 biomarker and tumor suppressor function, we analyzed its expression pattern in comparison to the prostate-specific biomarker NKX3.1. Immunohistochemistry-based ANXA7 and NKX3.1 protein expression was analyzed on human tissue microarrays of 4,061 specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 54 publications
1
38
0
Order By: Relevance
“…Showing a typical tumor suppressor gene pattern in our multitumor tissue microarray study, ANXA7 protein expression is consistently decreased in tumors (Srivastava et al, 2007). However, although reduced in androgen-resistant prostate cancers, ANXA7 is abundant in the adrenal gland, suggesting that its hormone-related expression could be coordinated with steroidogenesis and hormone sensitivity.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Showing a typical tumor suppressor gene pattern in our multitumor tissue microarray study, ANXA7 protein expression is consistently decreased in tumors (Srivastava et al, 2007). However, although reduced in androgen-resistant prostate cancers, ANXA7 is abundant in the adrenal gland, suggesting that its hormone-related expression could be coordinated with steroidogenesis and hormone sensitivity.…”
Section: Introductionmentioning
confidence: 61%
“…ANXA7 is specifically reduced in androgen-resistant prostate tumors (Srivastava et al, 2007). In the meantime, wild-type ANXA7 decreases and dominant-negative DN-ANXA7 increases low-molecular weight AR in androgen-sensitive LNCaP (Torosyan et al, 2009).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…4 However, exogenous WT-ANXA7 was capable of overcoming androgen-resistant status in vitro in both DU145 and PC3. By targeting AR, WT-ANXA7 represented a potential alternative to antiandrogens which may promote tumor invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Ca 21 -activated GTPase activity as well as involvement in membrane fusion and exocytosis, ANXA7 demonstrated tumor suppressor function in murine model 1 and in human prostate and breast cancers. 2,3 Our large-scale study on ANXA7 protein expression in different cancers 4 identified a drastic ANXA7 loss in the hormone-refractory prostate cancers as well as an abundant ANXA7 presence in the adrenal gland, a major source of sex hormone precursors. Although tumor suppressor mechanisms of ANXA7 are not yet elucidated, these data suggested that ANXA7, which has androgen-receptor (AR) regulatory elements in its promoter, may be involved in the regulation of androgen-dependent cell survival in prostate cancer cells.…”
mentioning
confidence: 99%